العوامل المؤثرة فاعلية التدقيق التدقيق الداخلي في القطاع الحكومي في إمارة دبي بدولة الإمارات العربية لمتحدة - Hussain Khalil Ashemsi
Internal audit has become one of the most important instruments that helps organizations control their functions and achieve their goals, and it has gained international attention by setting international standards for internal auditing. The research paper aims mainly to identify the factors affecting the efficiency of internal audit in the government sector in the Emirate of Dubai, the United Arab Emirates, through measuring the degree of compatibility of its internal audit practices with the International Standards for the Professional Practice of Internal audit issued by the Institute of Internal Auditors (IIA) in 2017. The research population consisted of auditors working in the internal audit units in the Government of Dubai, which consist of 46 departments, authorities, institutions, and government centers. To achieve the objectives of the research and examine its hypotheses, the research adopted the descriptive analytical approach, and the quantitative method using a questionnaire specifically designed as the main tool for collecting primary data and information, besides the qualitative method by conducting interviews with a number of managers of internal audit units and asking them questions and then analyzing the answers. Among the most important findings of the research: There is a statistically significant effect of the personal qualities of the internal auditor on the efficiency of internal audit in the government sector in the Emirate of Dubai (Direct effect), while the support for top-level management and organizational culture has no statistical significance, and their impact on the efficiency of internal audit in the government sector in Dubai is weak as a direct effect. However, it was found that there is a positive effect between the personal characteristics of the internal auditor and the support of top-level management with organizational culture, on the effectiveness of internal auditing, through the mediation relationship with compliance with internal audit standards. Thus, when the mediation complied with the international audit standards, the impact of the personal qualities, and values of the internal auditor as well as the support of top-level management and organizational culture increases the efficiency of internal audit. Furthermore, the interviews indicated the impact of the internal auditor’s personal qualities on the efficiency of internal audit, the most important of such qualities include honesty, integrity, impartiality, objectivity, accuracy, academic qualification, and professional certificates. In addition, the support of top-level management enhances the independence of the internal auditor and is important for implementing the recommendations of audit reports. As well as the efficiency of the organizational culture by applying transparency, accountability, and the separation of tasks and powers. Moreover, it was found that government sectors apply international standards reasonably. The study contributed to confirming that the more attention paid to the personal qualities and values of internal auditors, the higher the efficiency of internal auditing, On the other hand, there are risks threatening the independence of the internal auditor, such as: lack of competencies and limited expertise. However, there is a positive role for international standards in motivating government organizations in the Emirate of Dubai to follow and implement of normative requirements in the standards of the qualities required for internal auditors.